Principles of agricultural economics - Barkley, Andrew P., 1962-; Barkley, Paul W. (New York, NY : Routledge, 2020)
"Principles of Agricultural Economics, now in its third edition, con tinues to showcase the power of economic principles to explain and pred ict issues and current events in the food, agricultural, and agribusine ss sectors. This key text introduces economic principles in a succinct and reader-friendly format, providing students and instructors with a c lear, up-to-date, and straightforward approach to learning how a market -based economy functions, and how to use simple economic principles for improved decision making. The field of agricultural economics has expa nded to include a wide range of topics and approaches, including macroe conomics, international trade, agribusiness, environmental economics, n atural resources, and international development and these are all intro duced in this text. For this edition, new and enhanced material on agri cultural policies, globalization, welfare analysis, and explanations of the role of government in agriculture and agribusiness is included. Re aders will also benefit from an expanded range of case studies and text boxes, including more international cases, which discuss real world ex amples and issues including global hunger, biofuels, trade wars, agrito urism, and climate change. This book is ideal for courses on agricultur al economics, microeconomics, rural development and environmental polic y. The work is fully supported by a companion website which provides us ers with extra content to enhance their learning and further their unde rstanding of agricultural economics. Additional materials include flash cards, study guides, PowerPoints, multiple choice questions, essay que stions, and an instructor's manual"--
Includes bibliographical references and index.
Keywords: Agriculture -- Economic aspects -- United States